Network Performance Optimization Using Odd and Even Dual Interleaving Routing Algorithm for Oil and Gas Piepline Network - Lee, M. Y.; Azman, A. S.; Subramaniam, Siva Kumar; Feroz, F. S. (Universitas Ahmad Dahlan, 2022)
The oil and gas industry is one of the world’s largest conglomerates, involving the production of complicated and critical methods for refining. This indicates the high necessity for a secure and reliable system, such as the Wireless Sensor Network (WSN), which provides auspicious and flexible solutions for the industry. It is one of the most excellent and trendy solutions to the crisis existing within the oil and gas industry, especially in the midstream pipeline. In this application, the nodes were arranged in a linear architecture, to cover a long distance of the pipe. The factors causing the degradation of the overall network performance with increasing density were also identified, due to the increment of the load causing clogging and inhabiting the packet queue. This subsequently led to packet loss, throughput unfairness, higher power consumption, and passive nodes’ presence in the network. The proposed routing protocol (AODVEO) was also reactive based on the AODV reducing the instabilities by splitting the traffic into even and odd paths. Additionally, the performances of AODV and DSDV were used to benchmark the efficacy of the proposed routing protocol.